The Relationship between Receptive and Productive Knowledge: A Comparative Case Study of Second Language Vocabulary Acquisition between Four Children of Different Ages - Laiho, Katariina (My University, 2017)
In the present longitudinal case study, the early second language (L2) vocabulary acquisition of young Finnish learners of English was studied in order to examine the relationship between their receptive and productive vocabulary knowledge. In addition to comparing the sizes of these two vocabulary types, the purpose of the present study was to consider whether age and the target language (TL) learning environment add another dimension in explaining the differences in children’s success in L2 vocabulary acquisition. The present study observed and assessed the vocabulary acquisition of four young siblings of different ages. The subjects’ incremental L2 vocabulary knowledge from zero through partial to precise was studied for a year during their stay abroad in the United States. The study used mixed methods, i.e. it covered both quantitative and qualitative research. The data comprised interviews providing test results measuring the subjects’ receptive and productive vocabulary sizes as well as the subjects’ self-reflection of their own learning. The results of the present study suggest that age and the TL learning environment had an impact on the subjects’ early L2 vocabulary acquisition: the older subjects seemed to acquire new receptive vocabulary faster than younger learners as a result of explicit learning capabilities and a greater amount of TL input they were exposed to. In accordance with previous research findings, all the subjects’ receptive vocabulary knowledge tended to precede productive knowledge, and the older the subject was, the greater her receptive vocabulary knowledge seemed to be. However, the differences between the subjects’ receptive and productive vocabulary sizes appeared to vary to a great extent. More precisely, the development of productive vocabulary knowledge did not seem to follow the same pattern as receptive knowledge. On the contrary, younger children tended to progress faster than the oldest subject towards the end of the research period. As a result, productive vocabulary knowledge did not appear to be commensurate with age but dependent on other factors instead. Due to the small sample size of the present study, its findings are not generalizable, but they provide an insight to the phenomenon on an individual level. To draw reliable conclusions of the relationship between receptive and productive knowledge and the effects of age and the TL context on SLA, more research focusing on the connections of these factors is needed in this research field.